The Quality of Education as Reviewed from the Influence of Academic Supervision and the School Environment - Purwanti, Ana; Harapan, Edi; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the individual and combined effects of academic supervision and school environment on education quality in public elementary schools across Mesuji District, addressing three key objectives: (1) assessing academic supervision's impact, (2) evaluating school environment's influence, and (3) measuring their synergistic contribution. Employing a quantitative causal design, we surveyed 122 teachers from 10 systematically sampled public elementary schools (representing 44% of the district's 277 teachers across 25 schools). Data collection combined validated questionnaires (α=0.87) with institutional documentation, analyzed through Pearson correlation and hierarchical multiple regression (p<0.05). Findings reveal significant positive influences: academic supervision independently accounted for 32% variance in education quality (β=0.47, p<0.01), while school environment explained 28% (β=0.42, p<0.01). Their combined effect explained 67% of quality variance (R²=0.67, F=58.34, p<0.001), demonstrating synergistic enhancement beyond individual factors. This study introduces an integrated quality predictor model that: (1) quantifies the multiplier effect of combining supervision and environmental factors, and (2) establishes threshold values for effective supervision in resource-constrained settings - a previously unmeasured dimension in developing educational contexts. Three actionable strategies emerge: Implementing fortnightly supervision cycles with classroom observation protocols Optimizing physical environments through noise-reduction and learning space redesign Developing school climate improvement teams to monitor psychosocial factors. The research makes dual contributions by: (1) advancing theoretical understanding of environmental-supervisory interactions in educational ecosystems, and (2) providing an evidence-based framework for simultaneous quality improvement interventions in comparable rural school systems.